2019
DOI: 10.1002/acm2.12741
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of effective imaging dose and excess absolute risk of secondary cancer incidence for four‐dimensional cone‐beam computed tomography acquisition

Abstract: This study was conducted to estimate the organ equivalent dose and effective imaging dose for four‐dimensional cone‐beam computed tomography (4D‐CBCT) using a Monte Carlo simulation, and to evaluate the excess absolute risk (EAR) of secondary cancer incidence. The EGSnrc/BEAMnrc were used to simulate the on‐board imager (OBI) from the TrueBeam linear accelerator. Specifically, the OBI was modeled based on the percent depth dose and the off‐center ratio was measured using a three‐dimensional (3D) water phantom.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Although significant work has been accomplished in reducing the imaging dose of 4D‐CBCT, it is still substantially higher than 3D‐CBCT (just as 4D‐CT is to 3D CT) and can pose additional stochastic risk 325,326 . This coupled with the studies reporting underestimations of lung target motion ranges still prevalent with 4D‐CBCT, 327,328 supports the notion of having in‐room guided dynamic MR imaging to provide non‐ionizing and superior image contrast capabilities for target localization 329,330 .…”
Section: Daily Image Guidance Of Lung Treatmentsmentioning
confidence: 82%
“…Although significant work has been accomplished in reducing the imaging dose of 4D‐CBCT, it is still substantially higher than 3D‐CBCT (just as 4D‐CT is to 3D CT) and can pose additional stochastic risk 325,326 . This coupled with the studies reporting underestimations of lung target motion ranges still prevalent with 4D‐CBCT, 327,328 supports the notion of having in‐room guided dynamic MR imaging to provide non‐ionizing and superior image contrast capabilities for target localization 329,330 .…”
Section: Daily Image Guidance Of Lung Treatmentsmentioning
confidence: 82%
“…This was in line with the study by Aw-Zoretic et al (2014), in the younger age groups, where the E in CT brain in contrast with the older age groups was higher. This contributed to safety concerns as E was a factor in the assessment of the biological effects of radiation on patients [29]. Recent studies have confirmed a strong correlation between CT and carcinogenic risk radio-exposure, particularly in pediatric patients [9,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…For a Truebeam thorax kV CBCT the additional dose would be less than 2% of the prescribed dose (when prescribing 100 cGy) at any point of the field of view [55][56][57]. However, higher values have also been reported for a thorax kV CBCT using other linacs and protocols [27][28][29][30][31]. MV CBCT or portal MV image can also result in higher doses [28].…”
Section: Cancer Sitementioning
confidence: 99%